Late prehistory and protohistory, Volume 9, Sessions A3c and A16a Bronze Age and Iron Age : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain) - Coimbra, Fernando 1956-; Delfino, Davide 1976-; Sîrbu, Valeriu 1950-; Schuster, Cristian 1959- (Archaeopress Archaeology, 2016)
This work contains the proceedings of two sessions from the XVII UISPP World Congress, 2014
Previously issued in print: 2016. - Conference proceedings. - Includes bibliographical references
The emergence of warrior societies and its economic, social and environmental consequences / edited by Fernando Coimbra and Davide Delfino -- Aegean - Mediterranean imports and influences in the graves from continental Europe - Bronze and Iron Ages / edited by Valeriu Sîrbu and Cristian Schuster
Keywords: Bronze age / Europe / Congresses; Iron age / Europe / Congresses; Grabbeigabe; Eisenzeit; Import; Bronzezeit; Krieger; Europe / Antiquities / Congresses; Mittelmeerraum; Europa; Kontinentaleuropa; Konferenzschrift -- 2014 -- Burgos